Paired sensitivity analysis of four SARS-CoV-2 serological immunoassays in a longitudinal cohort of convalescent hospital staff. (November 2021) - Sim, Marcus; Cockcroft, Christopher; Darby, Denise; Ellis, Clare R; Heaps, Adrian; Scargill, Jonathan; Garcez, Tomaz
Background: SARS-CoV-2 serological testing has seen extensive academic and clinical use from investigating correlates of immunity to seroprevalence, convalescent plasma and vaccine trials. Interpretation of these studies will depend on robust validation of the longitudinal sensitivities of these assays, especially in the context of mild disease which makes up the majority of the Coronavirus Disease 2019 (COVID-19) caseload. Methods: Hospital staff ( n = 94) returning to work following polymerase chain reaction confirmed COVID-19 were offered antibody testing to assist with laboratory verification. Initial specimens were collected at median 29 days post-symptom onset and run on the Roche, Abbott, Siemens and DiaSorin platforms. Re-sampling occurred at median 142 days from a subset of the initial cohort ( n = 62) that had volunteered to provide further serum samples to assist in longitudinal sensitivity analysis. Samples that were not run across all four platforms were excluded from analysis. Results: Comparative sensitivity analysis was conducted on 89/94 of the initial specimens and 55/62 of the repeat specimens. Sensitivity at initial sampling ranged from 78 to 87% across platforms. At re-sampling, sensitivities were: 100% (Roche), 45% (Abbott), 100% (Siemens), and 80% (DiaSorin). Paired analysis using the longitudinal cohort ( n = 55) demonstrated stable or increasing median assay values on three platforms, with a clear reduction seen only on the Abbott platform (4.78 to 1.34) with corresponding sensitivity drop-off (81.8% to 45.4%). Conclusion: The Abbott assay demonstrated sensitivity drop-off and decrease in median assay signal below detection threshold at four to five months. This has implications on the interpretation and design of future studies.